Sorgum Agar (Sorghum bicolor) as Substitute Nutrient Agar Media for Cultivation Escherichia coli - Pestariati Pestariati; Mufidah Mufidah (Humanistic Network for Science and Technology (HNST), 2021)
Media (nutrient agar) is a medium that is often used for bacteriological examinations and the price is relatively more expensive, Sorghum bicolor materials that are easy to get and cheap. Sorghum contains carbohydrates and protein which are suitable for manufacturing agar nutrients. This research was an experimental quantitative analysis laboratory. The research used Sorghum bicolor flour as carbohydrates and proteins in nutrient agar media. This study used variations in the mass of sorghum flour 2.50 grams, 3.75 grams, 5.00 grams, and 6.25 grams. The average number of bacterial colonies at mass variations was 2.50 grams, 3.75 grams, 5.00 grams, and 6.25 grams, namely 70.75 × 1013 CFU / mL, 60.75 × 1013 CFU / mL, 49, 25 × 1013 CFU / mL, and 42 × 1013 CFU / mL with significant differences in the value of p = 0.000 or